Modern Methods Of Treatment Of Chronic Hematogenous Osteomyelitis In Children - Musoyev Sodiqjon Toyirovich (Journal of Science in Medicine and Life, 2024)
Chronic hematogenous osteomyelitis (CHO) develops after an acute disease and is characterized by a long-term course alternating with periods of exacerbation and remission (relative well-being). The morphological substrate for this course of the disease, as a rule, is the bone area that has died as a result of acute inflammation. Over time, it is rejected by living bone and a sequestration is formed, which is usually located in the bone cavity - a sequestration box. A common component of CHO is purulent fistulae, which are pathological transitions in the tissues that connect the osteomyelitis cavity with the external environment. A fistula usually opens in the skin with an external hole and is a type of drainage that drains the excess pus formed into the external environment. Being an absolute pathology, fistula, nevertheless, sometimes allows the patient to live for many months and years with minimal manifestations of the inflammatory process. When the fistula is closed or cannot drain the pathological intraosseous lesion, conditions are created for the disease to worsen. Pain appears or increases, temperature rises, local signs of an acute inflammatory process (swelling, redness, etc.) are observed. In the future, paraosseous phlegmon may develop or the purulent fistula will reopen. As a rule, patients with chronic exacerbation of the gastrointestinal tract seek emergency medical care. Timely assistance in such a case causes the risk of spread of the purulent process to the surrounding tissues, increased intoxication and the development of sepsis.